TURNOVER FACTORS ANALYSIS IN BUSINESS ORGANIZATION - maskarto lucky nara rosmadi (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
This study aims to determine the factors causing the turnover of a business organization. The method used was quantitative with a descriptive-analytical approach, with 333 respondents. Data collection in this research was conducted by questionnaire technique and documentary study. The Data Obtained is then processed using SPSS version 23.00. From the results of the data show, the contribution given by career development is 23.40%, equal to 17.90% of welfare, equal to 21.50% workload, and health safety equal to 21.20% to turnover. While the rest of 21.20% is another factor that is not researched. Keywords: Career development, Welfare, Workload, Occupational safety, and health.